Evaluation of the histamine H3 receptor antagonists from LINS01 series as cholinesterases inhibitors: Enzymatic and modeling studies - Lopes, Flávia B.; Aranha, Cecília M. S. Q.; Corrêa, Michelle F.; Fernandes, Gustavo A. B.; Okamoto, Debora N.; Simões, Leonardo P. M. [UNESP]; Junior, Nailton M. N. [UNESP]; Fernandes, João Paulo S. (Wiley, 2022)
Histamine is involved in several central nervous system processes including cognition. In the last years, H3 receptor (H3R) antagonists have been widely explored for their potential on dementias and other cognitive dysfunctions, and the cooperative role between histamine and acetylcholine neurotransmissions on cognitive processes is widely known in literature. This motivated us to assess the potential of 1-[(2,3-dihydrobenzofuran-1-yl)methyl]piperazines (LINS01 compounds) as inhibitors of cholinesterases, and thus this work presents the inhibitory effect of such compounds against acetyl (AChE) and butyrylcholinesterase. A set of 16 selected compounds were evaluated, being compounds 2d and 2e the most potent inhibitors of both cholinesterases (IC50 13.2–33.9 μM) by competitive mechanism, as indicated by the kinetic assays. Molecular docking simulations suggested that the allylpiperazine and dihydrobenzofuran motifs present in these compounds are important to perform π-interactions with key tryptophan residues from the enzymes, increasing their affinity for both H3R and cholinesterases. Metric analysis support that compound 2d (LINS01022) should be highlighted due to its balanced lipophilicity (ClogP 2.35) and efficiency (LE 0.32) as AChE inhibitor. The results add important information to future design of dual H3R-cholinesterases ligands.
Keywords: Alzheimer's disease; cholinesterase inhibitor; designed multitarget ligand; histamine H3 antagonist; procognitive agent